2008
DOI: 10.1002/jor.20791
|View full text |Cite
|
Sign up to set email alerts
|

Improving vastus medialis obliquus function reduces pressure applied to lateral patellofemoral cartilage

Abstract: The current study was performed to characterize how improving vastus medialis obliquus (VMO) function influences the pressure applied to patellofemoral cartilage. An additional focus was characterizing how lateral and medial cartilage lesions influence cartilage pressures. Ten knees were flexed to 408, 608, and 808 in vitro, and forces were applied to represent the VMO and other muscles of the quadriceps group while a thin film sensor measured joint pressures. The knees were loaded with a normal VMO force, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 36 publications
4
66
0
1
Order By: Relevance
“…The contact area between the patella and the femur begins on the distal patella and migrates proximally during knee flexion [32,40]. Draper et al found that if the articular surface of the patella is divided into three regions-proximal, middle, and distal-the middle region is the area with the thickest articular cartilage [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact area between the patella and the femur begins on the distal patella and migrates proximally during knee flexion [32,40]. Draper et al found that if the articular surface of the patella is divided into three regions-proximal, middle, and distal-the middle region is the area with the thickest articular cartilage [12].…”
Section: Discussionmentioning
confidence: 99%
“…(6.4 mm) thick neoprene rubber (McMaster-Carr; Elmhurst, Illinois) was placed on either side of the sensor during calibration to simulate the compliance provided by patellofemoral cartilage [32][33]. The sensor and rubber sheets were placed under the testing platform between two steel plates to produce an area of nearly uniform pressure [32]. Following preconditioning with three loads to a minimum of 5,000 N applied over 10 seconds, a series of five loads ranging from 100 to 5,000 N were applied to the sensor, according to manufacturer guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Optimal PFJ biomechanics relies on the interaction between the vastus medialis obliquus (VMO) and vastus lateralis 109. Inhibition or delayed onset of the VMO occurs in the presence of knee pain110 111 and effusion,112 113 which is common after ACLR 36.…”
Section: Proposed Contributors To Pfj Oa Development After Aclrmentioning
confidence: 99%
“…Systematic examinations of the effect of asymmetric quadriceps loading on patellar motion only exist in vitro [4,[9][10][11][12]. However, the experimental setups used in former in vitro studies only enabled the simulation of constant muscle forces over the whole flexion range.…”
Section: Introductionmentioning
confidence: 99%